Calculated Correction of the General Seismic Hazard Rate for an Example of Territory of the City of Salavat, Republic of Bashkortostan - D. Yu. Shulakov; O. N. Kovin; Yu. V. Baranov (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2022)
In course of the study, an analysis of the regional earthquake catalogues, issued by different institutions, was fulfilled providing the basis for determination of the seismic regime parameters and regional macroseismic equation on the area of investigation. The obtained data made it possible to calculate the corrected value of general seismicity rate for territory of the city of Salavat, Bashkortostan.